The Penalty-Duel and Institutional Design: Is there a Neeskens-Effect? - Wolfgang Leininger; Axel Ockenfels (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
We document an increase in the scoring probability from penalties in soccer, which separates the time period before 1974 significantly from that after 1976: the scoring probability increased by 11%.We explain this finding by arguing that the institution of penalty-shooting before 1974 is best described as a standard of behaviour for striker and goal-keeper, which in game-theoretic terms represents a 2x2-game. In contrast to this, after 1976 the institution of the penalty-duel is best described by a 3x3 game form constrained by certain behavioural rules. Those rules can be parameterized by a single parameter, which nevertheless allows the theoretical reproduction (and hence explanation) of all the empirically documented regularities.The scoring probability in equilibrium of the latter institution is higher than in the former one.We present historical evidence to the effect, that this change in the perception of penalty- duels (as two different games), was caused by Johan Neeskens' shrewd and 'revolutionary' penalty-taking during World-Cup 1974, when he shot a penalty in the first minute of the final between Germany and the Netherlands right into the middle of the goalmouth.
Keywords: D01; C72; D74; C93; 330; Professional soccer; mixed strategy equilibrium; institutional design; Fußballsport; Spieltheorie; Institutionalismus; Theorie; Deutschland